"We wonder if white peers even want to understand": Social Work Students' Experiences of the Culture of Human Interchange. (2nd January 2023) - Keyes, Tasha Seneca; Hendrix, Elizabeth; Tecle, Aster; Andino, Christina; Bitters, Brittany; Carter, Rachel; Koelling, Elisabeth; Ortiz, Emily; Sanchez, Michelle; Ota, Irene; Gringeri, Christina
ABSTRACT: Diversity curriculum supports students in becoming critically reflexive social workers and advancing their multicultural practice. Often unexamined is how students perceive the explicit curriculum about race and racism and experience the implicit curriculum through the culture of human interchange. Ninty-three social work students completed a survey about their experiences in diversity classes. Using qualitative methods, we examine how students experienced the culture of human interchange in discussions of race and racism. Two themes influence the culture of human interchange: are to the disconnect in instructional praxis, and the contested terrain between marginalized and privileged identities. Implications for instructors have knowledge about U.S. history of race and racism and the systemic barriers for people of color, and to engage in self-reflection.